Metabolic Dysfunction-Associated Fatty Liver Disease and Fibrosis Status in Patients with Type 2 Diabetes Treated at Internal Medicine Clinics: Türkiye DAHUDER Awareness of Fatty Liver Disease (TR-DAFLD) Study - Şahintürk, Yasin; Köker, Gökhan; Koca, Nizameddin; Sümbül, Hilmi Erdem; Demir, İsmail and Keskin, Havva and Yaylacı, Selçuk and Solmaz, İhsan and Açmaz, Banu and Yıldız, Hamit and et al. (Turkish Journal of Gastroenterology, 2024)
Background/Aims: This awareness study aimed to determine the ultrasound (US) examination rates in relation to US-confirmed metabolic dysfunction-associated fatty liver disease (MAFLD) diagnosis in internal medicine outpatients with type 2 diabetes (T2D) across Türkiye. Materials and Methods: A total of 6283 T2D patients were included in this multicenter retrospective cohort study conducted at 17 internal medicine clinics across Türkiye. The presence and indications for US performed within the last 3 years were recorded along with US-confirmed MAFLD rates, laboratory findings on the day of US, and referral rates. Fibrosis-4 (FIB-4) index was calculated to estimate the risk of advanced liver fibrosis (FIB-4 index ≥ 1.3). Results: Overall, 1731 (27.6%) of 6283 patients had US examination, which revealed MAFLD diagnosis in 69.9% of cases. In addition, 24.4% of patients with US-confirmed MAFLD were at risk of advanced fibrosis (FIB-4 index ≥ 1.3), and the referral rate was 15.5%. Conclusion: In conclusion, our findings emphasize an insufficient MAFLD awareness among clinicians and the likelihood of most of T2D patients to be at risk of living with an unknown status regarding their MAFLD and advanced fibrosis risk. Cite this article as: Şahintürk Y, Köker G, Koca N, et al. Metabolic dysfunction-associated fatty liver disease and fibrosis status in patients with type 2 diabetes treated at internal medicine clinics: Türkiye DAHUDER awareness of fatty liver disease (TR-DAFLD) study. Turk J Gastroenterol. 2024;35(8):643-650.